The Vetigastropoda (Mollusca) of Walters Shoal, with descriptions of two new genera and thirty new species - Herbert, David G. (European Journal of Taxonomy, 2024)
The vetigastropod material collected on Walters Shoal during Cruise MD208 of the Tropical Deep-Sea Benthos programme is documented. In total, 50 species were obtained, 30 of which are new and apparently endemic to the seamount. Of the other 20 species, eight are regionally endemic to the south-western Indian Ocean, 11 are more widely distributed in the Indo-West Pacific and one is possibly of deep-water Atlantic origin. The primary affinities of the fauna are with warm temperate South Africa and the tropical western Indian Ocean, but one species is potentially a seamount endemic of southern affinity. A new pseudococculinid genus living on decomposing bird feathers is described, a biogenic substrate association previously unknown in the Mollusca. The following new genera are described: Imbricoscelis gen. nov. and Pterodacna gen. nov. The following new species are described: Akritogyra crenulata sp. nov., Bathymophila williamsae sp. nov., Benthobrookula araneum sp. nov., Be. galeneae sp. nov., Be. laticostata sp. nov., Be. scalaroides sp. nov., Be. semisculpta sp. nov., Bruceina areneformis sp. nov., Calliostoma pantopunctatum sp. nov., Cantrainea herosae sp. nov., Carinastele achrosta sp. nov., Cornisepta marshalli sp. nov., Emarginula lentiginosa sp. nov., E. nodulicostata sp. nov., E. retrogyra sp. nov., E. salebrosa sp. nov., Fluxinella dufresneae sp. nov., Gibbula roseosticta sp. nov., Hadroconus scobina sp. nov., Kaiparathina monticola sp. nov., Lissotesta wareni sp. nov., Microcollonia miniata sp. nov., Mikro crassus sp. nov., Parviturbo cicatricosus sp. nov., Phragmomphalina candida sp. nov., Pterodacna boucheti gen. et sp. nov., Solariella asaphea sp. nov., Spinicalliotropis lepidota sp. nov., Stomatella multilirata sp. nov. and Trenchia mcleani sp. nov. The following new combinations are proposed: Brookula coronis Barnard, 1963 is transferred to Imbricoscelis gen. nov., Cantharidus nolfi Poppe, Tagaro & H. Dekker, 2006 is transferred to Kaiparathina Laws, 1941 and Solariella incisura Melvill, 1909 is transferred to Phragmomphalina Herbert & Williams, 2020. The following new synonyms are proposed: Carinastele wareni Vilvens, 2014 is a synonym of Bruceina cognata (Marshall, 1988); Fluxinella stellaris Bozzetti, 2008 is a synonym of Agagus stellamaris Herbert, 1991.